Die teken van Jona en Jesus as Messias - Deist, Ferdinand (Verbum et ecclesia, 1993)
The sign of Jonah and Jesus as Messiah Jewish tradition and the contexts in which Matthew and Luke refer to the "sign of Jonah" suggest that the sign demanded of Jesus by the authorities should prove his prophetic authority for deviating from traditional Torah. In the light of Jewish tradition on Jonah ben Amittai as the (Ephraimite) Messiah ben Joseph the mention of the sign itself may suggest that, at least in Matthew, Jesus claims messianic authority, and implies his eschatological victory over all evil powers, leading to the messianic banquet of believers.